(untitled) (Journal of Information Technologies in Education (ITE), 2008)
In the article basic problem questions and tasks on the use of information-communication technologies in public authority’s activity and at preparation of government employee are expounded. A sequence on introduction of information-communication technologies in administrative activity and examples of computer literacy acquirement in accordance with the ECDL standards within the framework of collaboration with the European partners is resulted.